2016
DOI: 10.1016/j.bbrc.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

S -Nitrosylated fetal hemoglobin in neonatal human blood

Abstract: Background Nitric oxide (NO) and its derivatives play important roles in the cardiopulmonary transition upon birth and in other oxygen-sensitive developmental milestones. One mechanism for the coupling of oxygen sensing and signaling by NO species is via the formation of an S-nitrosothiol (SNO) moiety on hemoglobin (Hb, forming SNO-Hb) and its release from the red blood cell in hypoxia. Although SNO-Hb formed on adult-type Hb (HbA, forming SNO-HbA) has been documented in physiological and pathophysiological hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In particular, RBCs from a mouse model bearing human hemoglobin in which the β93 Cys residue was mutated to Ala (alanine) were reported to function normally. But this mouse was also engineered to express gamma hemoglobin [a component of fetal hemoglobin (HbF)], which we have shown is also reversibly S-nitrosylated ( Riccio et al, 2016 ); this rescue may account for the lack of phenotype in this mouse. By contrast, Zhang and coworkers demonstrated that even the persistence (or presence by knock-in) of SNO-susceptible fetal hemoglobin does not fully compensate for the mutation of the critical Cys normally present at residue 93 of the beta-globin subunit of hemoglobin ( Zhang et al, 2015 ).…”
Section: Red Blood Cells In Disease Statesmentioning
confidence: 99%
“…In particular, RBCs from a mouse model bearing human hemoglobin in which the β93 Cys residue was mutated to Ala (alanine) were reported to function normally. But this mouse was also engineered to express gamma hemoglobin [a component of fetal hemoglobin (HbF)], which we have shown is also reversibly S-nitrosylated ( Riccio et al, 2016 ); this rescue may account for the lack of phenotype in this mouse. By contrast, Zhang and coworkers demonstrated that even the persistence (or presence by knock-in) of SNO-susceptible fetal hemoglobin does not fully compensate for the mutation of the critical Cys normally present at residue 93 of the beta-globin subunit of hemoglobin ( Zhang et al, 2015 ).…”
Section: Red Blood Cells In Disease Statesmentioning
confidence: 99%
“…Second, l ‐CSNO and other S‐nitrosothiols appear to also play a role in the perinatal transition to air‐breathing 65 . Human HbF carries significant S‐nitrosothiol signaling potential, in addition to HbA, 66 , 67 and because the P 50 of HbF is lower (its oxygen affinity is higher), the oxygen tension at which NO is transferred to form S‐nitrosothiols is higher. Oxygen tensions are quite low before birth, shifting dramatically at birth.…”
Section: Potential Implications For Respiratory Control In Childrenmentioning
confidence: 99%